ChemInform Abstract: Transition‐Metal‐Catalyzed Laboratory‐Scale Carbon—Carbon Bond‐Forming Reactions of Ethylene. Issue 6 (11th February 2014) - Saini, Vaneet; Stokes, Benjamin J.; Sigman, Matthew S.
Abstract Review: 74 refs.